Level of Anxiety, Confidence and Concentration of Shooting Athletes in Makassar City - Hasyim, Muhammad Qasash; Fahrizal, Fahrizal; Syamsuddin, Muh. Syachrul (SHOOTING: Journal of Sport, Health, and Education, 2023)
This research is a descriptive study that aims to categorize anxiety levels, confidence levels, and concentration levels in shooting athletes in Makassar city. There are three variables in this study are anxiety, self-confidence, and concentration of shooting athletes in Makassar city. The population in this study were all South Sulawesi shooting athletes, while the sample was Makassar city shooting athletes with a total of 30 athletes. Based on the results of the analysis it can be concluded that at the anxiety level there are 36.7% of athletes have a low level of anxiety, 53.3% of athletes have a moderate level of anxiety, and 10% of athletes have a high level of anxiety, while at the level of self-confidence there are 86.7% of athletes have a high level of self-confidence, 13.3% of athletes have a moderate level of self-confidence and no athletes have a low level of self-confidence, and at the concentration level there are 3.3% of athletes have a very good level of concentration, 23.3% of athletes have a moderate level of concentration, 40% of athletes have a poor level of concentration and 30% of athletes have a very poor level of concentration.